Exploring Delphi Method Utilization Research Trends on Public-Private Partnership Infrastructure Studies - Sunandar, Ali; Abd Karim, Saipol Bari; Zolkafli @Zulkifly, Umi Kalsum (PT Penjaminan Infrastruktur Indonesia (Persero), 2025)
This study seeks to explore the application of the Delphi method in Public-Private Partnership (PPP) infrastructure research over a ten-year span (2015-2024), with a focus on various characteristics such as the application of the Delphi method across different PPP infrastructure sectors, expert criteria for Delphi panels, the diverse use of consensus, and the execution of Delphi rounds. Employing a Systematic Literature Review (SLR) guided by the PRISMA framework, the study utilizes thematic categories alongside co-occurrence and co-authorship analyses to identify trends in the application of the Delphi method in PPP infrastructure studies. The review concentrates on literature indexed in two leading academic databases: Web of Science (WoS) and Scopus. The findings indicate that the use of the Delphi method has grown significantly in the past ten years within infrastructure PPP schemes, particularly in emerging countries driven by the increasing demand for infrastructure development. Research trends have highlighted a variety of characteristics of the Delphi method, including criteria for selecting experts, the number of expert participants, the number of Delphi rounds, and different approaches for achieving consensus or agreement. These findings offer valuable insights to inform and enhance the methodological rigor of future research utilizing the Delphi method in the context of PPP infrastructure.